The importance of institutions and policy settings for car sharing – Evidence from the UK, Israel, Sweden and Finland - Akyelken, Nihan; Givoni, Moshe; Salo, Marja; Plepys, Andrius; Judl, Jáchym; Anderton, Karen; Koskela, Sirkka (European Journal of Transport and Infrastructure Research, 2018)
The rapid growth of cities requires effective management of transport demand and restructuring of transport systems to address the needs of growing urban populations in an environmentally, socially and economically sustainable way. In recent years, car sharing has emerged as an alternative to owning cars in cities, which has potential to bring environmental gains and address social considerations. There is a sizeable academic inquiry about the social and environmental benefits of car sharing and the barriers to its introduction and provision in different empirical contexts. However, most research on the determinants of its uptake and the ease of provision remains limited to investigating consumer demand and how to realise the benefits of car sharing. Drawing on cases from the UK, Israel, Sweden and Finland, this paper focuses on the institutional and policy settings to understand the systemic barriers for car sharing services in diverse urban contexts to expand knowledge on the challenges to and the challenges that emerge from car sharing schemes.